Impact of employee training on guests satisfaction: a survey on 5 Star Hotels in Kuala Lumpur - Cheng, Fan Fah; Cheng, Seow Voon (American-Eurasian Network for Scientific Information, 2016)
Background: This study extended research on the importance of training and development for customer satisfaction and employee satisfaction by examining its influence on 5 Start Hotels. The survey was based on quantitative method, and 200 questionnaires were collected by using the random sampling method of convenience sampling at 5 Star hotel staffs in Kuala Lumpur. The findings showed that there is relation between employee training and customer satisfaction in five start hotel in Kuala Lumpur. Furthermore, successful training program has relationship to improve / influence employee satisfaction level.